Tindak Tutur Ilokusi dalam Berita "Program Vaksinasi Covid-19" Pada Laman Tribunnews.Com - Nisa, Choirul (Jurnal Simki Pedagogia, 2021)
This study aims to describe the form of illocutionary speech acts in the news "Covid-19 Vaccination Program" on the TribunNews.com page. The type of research used is qualitative research. Sources of data in this study are primary data sources and secondary data. The data in this study are all illocutionary speech acts used in the news (in writing) "Covid-19 Vaccination Program" on the TribunNews.com page. Data collection techniques used are documentation techniques, reading techniques, and note-taking techniques. The results showed: The types of illocutionary speech acts consist of (a) assertive form (stating number (28), complaining amounting to (8), suggesting amounting to (12), and informing amounting to (28)), (b) directive form (ordering totaling (13), advising amounting to (10), asking amounting to (11), ordering totaling (1)), (c) expressive form (thanks amounting to (4), praising amounting to (2), blaming amounting to (2)), (d) commissive form (promising amounting to (3), offering something amounting to (1)), (e) form of declaration (exclusion amounting to (1), raising amounting to (1), giving name amounting to (1), punishing amounting to (1) The results of the speech act data in this study found as many as seventy-five (76) assertive speech acts, thirty-five (35) directive speech acts, eight (8) expressive speech acts, four (4) four commissive speech acts, four declarations ( 4) speech act The most dominating speech act in the news "Covid-19 Vaccination Program" on the Tribune page News.com is an assertive illocutionary speech act as many as seventy five (76) speech acts.